Congenital Scoliosis and Tetralogy of Fallot With Neurodevelopment Delay: A Case Study and Literature Review - Yazdan Ghandi; Saeed Karimi; Rasool Karimi (Mazandaran University of Medical Sciences, 2022)
As the most common congenital heart malformation, tetralogy of Fallot (TOF) produces cyanosis. Patients with TOF suffer from a higher frequency of major noncardiac congenital disorders. Its association with congenital scoliosis influences vital and functional overcomes, restricting physical activity and lowering life expectancy. An 8-month-old female child was reported with admitted cough, fever, and ruled-out pneumonia. The child was diagnosed with heart disease at 2-month-old when cyanosis was apparent. After being admitted to a hospital, history and physical examination showed mild neurodevelopmental delays, such as an inability in rolling and crawling. Her chest x-rays revealed congenital spine abnormalities thoracic vertebral at T3-T8 levels and bilateral segmented-bar sacral vertebrae. Given that patients with TOF routinely undergo chest radiographs, physicians examining TOF patients' chest radiographs should be aware of the potential for congenital scoliosis to provide early diagnosis and referral for orthopedic evaluation and treatment.